Identities in plactic, hypoplactic, sylvester, Baxter, and related monoids - Cain, Alan J. (2019)
Supported by an Investigador FCT fellowship (IF/01622/2013/CP1161/CT 0001). This work was partially supported by the Fundacao para a Ciencia e a Tecnologia (Portuguese Foundation for Science and Technology) through the project UID/MAT/00297/2013 (Centro de Matematica e Aplicacoes), the project PTDC/MHC-FIL/2583/2014, and the project PTDC/MAT-PUR/31174/2017.